(Review A) "Pandemic, homo somatis, and Transformations of the Russian Orthodox Ethos" - Anonymous (CERES / KHK Bochum, 2021)
This is the first review of the preprinted article "Pandemic, homo somatis, and Transformations of the Russian Orthodox Ethos." The review will be taken offline once the final article has appeared. The reviewed article can be found under the following link: (PREPRINT) Pandemic, homo somatis, and Transformations of the Russian Orthodox Ethos | Entangled Religions (rub.de)